2021
DOI: 10.1002/slct.202103214
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Antimicrobial, Antibiofilm, Efflux Pump Inhibiting, and ADMET Properties of Newly Synthesized 1,3,4‐Thiadiazole Derivatives**

Abstract: The novel compounds bearing 1,3,4‐thiadiazole moiety were obtained and their structures were identified using FT‐IR, NMR methods, elemental, and mass analysis. UV‐Vis and fluorescence spectra were obtained in six different polarity solvents. In addition, antimicrobial, antibiofilm, and the efflux pump inhibiting activities of the new compounds on K. pneumoniae, methicillin‐resistant S. aureus (MRSA), E. coli, and C. albicans were investigated. Furthermore, druglikeness and ADMET properties of the compounds wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…Another research observed either no activity, weak or moderate activities of some 1,3,4-thiadiazole derivatives on E. coli (57). One of the previous studies published by our group presents that some of these derivatives had antimicrobial activities against C. albicans, and K. pneumoniae, but none of them were active against E. coli, which were the same strains used in this present study (24). These studies reveal that the results on the subject of the antibacterial and antifungal effects of the 1,3,4-thiadiazole derivatives were conflicting.…”
Section: Mic and Mbc/mfc Tests Resultssupporting
confidence: 48%
See 1 more Smart Citation
“…Another research observed either no activity, weak or moderate activities of some 1,3,4-thiadiazole derivatives on E. coli (57). One of the previous studies published by our group presents that some of these derivatives had antimicrobial activities against C. albicans, and K. pneumoniae, but none of them were active against E. coli, which were the same strains used in this present study (24). These studies reveal that the results on the subject of the antibacterial and antifungal effects of the 1,3,4-thiadiazole derivatives were conflicting.…”
Section: Mic and Mbc/mfc Tests Resultssupporting
confidence: 48%
“…The 1,3,4-thiadiazole compounds were investigated for antimicrobial activity against three microorganisms, namely Candida albicans DSMZ 1386, Escherichia coli (MDR), and Klebsiella pneumoniae (MDR). The strains used in this study were previously tested for their biofilm production capacities and efflux pump activities (24).…”
Section: Microorganismsmentioning
confidence: 99%
“…[6] In this context, the development of treatment and prevention procedure for infections depends on the efficiency of the antibiotics employed [7] and most antimicrobial agents, such as Furazolidone, Nitrofurantoin, and Nitrofurazone, bear a hydrazide/hydrazone moiety. [8] Hydrazides are a class of compounds that finds applications in pharmaceuticals (due to their multifaceted biological activities, including, among the others antibacterial, [9] antifungal, antiviral, antimalarial, diuretic, hormone antagonist, antioxidant, analgesic, hypoglycemic, and anti-inflammatory activities [10] and as surfactants. [11] Moreover, hydrazides are often versatile molecules that can be employed in the preparation of heterocyclic compounds, or as ligands in coordination chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Tey included the molecular weight (MW) 500, the octanol/water partition coefcient (A log P) 5, the number of hydrogen bond donors (HBDs), and the number of hydrogen bond acceptors (HBAs), all of which must be greater than or equal to 5 [49][50][51]. Ghose and colleagues calculated that, of the 6304 compounds in the CMC (comprehensive medicinal chemistry) database, more than 80% met the following requirements: −0.4 A log P 5.6, 160 MW 480, 40 MR (molar refractivity), and 20 to 70 atoms in total [52]. 7 drug development can be sped up by using flters that compare compounds to drugs based on their physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%